1985
DOI: 10.1111/j.1365-2621.1985.tb10539.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Amino Acid Composition of the Roe and Muscle of Selected Marine Species

Abstract: Crude protein, total lipid, water, cholesterol, and amino acid composition of the roe of eighteen Pacific marine species were determined and compared with those of muscle from the same marine species. Crude protein and total lipid were higher in roe than in muscle, while water was lower. Cholesterol in roe was generally tenfold higher than that of muscle but only around one-fourth that of hen egg yolk. Glutamic acid, leucine, and aspartic acid were generally found to be the major components of roe. Leucine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
72
6
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 8 publications
17
72
6
1
Order By: Relevance
“…Özyurt & Polat (2006) reported that the ratio of EAA to NEAA for wild sea bass were 0.75 and 0.77 for winter and summer respectively. According to other studies, the ratio of EAA to NEAA was 0.71 for cod Gadus morhua (Jhaveri et al, 1984) and mullet Mugil cephalus (Iwasaki & Harada, 1985); 0.74 for herring Clupea pallasi and 0.75 for chum salmon Oncorhynchus keta (Iwasaki and Harada, 1985). Similar ratios were obtained by and Valente et al (2011) in fillets of sea bream from other Mediterranean Regions in Europe.…”
Section: Amino Acid Content Of Sea Basssupporting
confidence: 65%
“…Özyurt & Polat (2006) reported that the ratio of EAA to NEAA for wild sea bass were 0.75 and 0.77 for winter and summer respectively. According to other studies, the ratio of EAA to NEAA was 0.71 for cod Gadus morhua (Jhaveri et al, 1984) and mullet Mugil cephalus (Iwasaki & Harada, 1985); 0.74 for herring Clupea pallasi and 0.75 for chum salmon Oncorhynchus keta (Iwasaki and Harada, 1985). Similar ratios were obtained by and Valente et al (2011) in fillets of sea bream from other Mediterranean Regions in Europe.…”
Section: Amino Acid Content Of Sea Basssupporting
confidence: 65%
“…The ratios of essential amino acids (EAA) to nonessential amino acids (NEAA) in black tiger shrimp were close to the average of 0.70 reported by Iwasaki & Harada [1985] but higher ratios were reported in shrimps and lobster [Rosa & Nunes, 2003]. Based on the ratio fresh, smoked and sundried P. monodon have adequate nutritional protein.…”
Section: Non-polar Fatty Acids Concentrationmentioning
confidence: 93%
“…The ratio of essential (E, mg/100 g )/nonessential (NE, mg/100 g) amino acids was observed to be 0.76 in autumn, 0.75 in winter and 0.77 in spring and summer (Özyurt and Polat, 2006). Contents of MAAs were low to almost undetectable during the ice-cover season, whereas they increased as the ice started to melt, and reached highest concentrations during the ice-free season (Tartarotti Iwasaki and Harada (1985). Table 4 shows the compositional characteristics in terms of carbohydrate and energy content of the different raw trout lots and the corresponding cultured and wild trout.…”
Section: Amino Acid Compositionmentioning
confidence: 99%